A Practitioner Concept of Contemporary Creativity. (December 2019) - Taylor, Stephanie
This article reviews conceptualizations from three academic areas: the sociology of art, the psychology of creativity, and research on the cultural and creative industries. These are compared with findings from a critical discursive study with UK practitioners. The meanings and associations these maker artists attach to creativity are discussed as a practitioner concept . For the practitioners, the association of creativity with art carries a promise of transcendence and escape from ordinary life but also a potential challenge to their own entitlement and claims to a creative status. These findings demonstrate that the academic areas utilize different and conflicting conceptualizations and, second, that the practitioner concept is not consistent with any one of these. In conclusion, the contemporary celebration of creativity is based on different meanings and unacknowledged conflicts. Future social psychological research on creativity requires a more critical approach to the concept.